The significance and the effects of the battle of Varna - Swoboda, Wincenty (Balcanica Posnaniensia. Acta et studia, 1997)
The article is devoted to a reinterpretation of the significance of the Battle of Varna of 1444 in European historiography. The author analyzes the problem of assessing the consequences of the defeat of the Christian forces and its place in the process of the Ottoman conquest of the Balkans. The article polemicizes with the view, firmly established in historiography, that the Battle of Varna was of decisive importance for Ottoman expansion in Southeastern Europe. The aim of the study is to challenge this traditional interpretation and to indicate that the capture of Constantinople in 1453 played a greater role. The author employs a critical analysis of Latin, Greek, and Turkish sources, including chronicles, letters, and Ottoman accounts of the wars of Murad II. The article demonstrates that, for the Ottomans, the Battle of Varna was merely one episode in the wars in Europe, similar to the Second Battle of Kosovo in 1448. The significance of Varna, however, was exaggerated in European historical memory because of the death of the young king Władysław III. The results of the analysis indicate that the decisive event for the fate of the Balkans was the Ottoman capture of Constantinople, while Varna had a more symbolic than strategic significance.